What is the optimal duration of home-video-EEG monitoring for patients with <1 seizure per day? A simulation study - Vander, Tatiana; Stroganova, Tatiana; Doufish, Diya; Eliashiv, Dawn; Gilboa, Tal; Medvedovsky, Mordekhay; Ekstein, Dana (Frontiers in Neurology, 2022)
Ambulatory “at home” video-EEG monitoring (HVEM) may offer a more cost-effective and accessible option as compared to traditional inpatient admissions to epilepsy monitoring units. However, home monitoring may not allow for safe tapering of anti-seizure medications (ASM). As a result, longer periods of monitoring may be necessary to capture a sufficient number of the patients’ stereotypic seizures. We aimed to quantitatively estimate the necessary length of HVEM corresponding to various diagnostic scenarios in clinical practice. Using available seizure frequency statistics, we estimated the HVEM duration required to capture one, three, or five seizures in different days, by simulating 100,000 annual time-courses of seizure occurrence in adults and children with more than one and less than thirty seizures per month (89% of adults and 85% of children). We found that the durations of HVEM needed to record 1, 3, or 5 seizures in 80% of children were 2, 5, and 8 weeks (median 2, 12, and 21 days), respectively, and significantly longer in adults - 2, 6 and 10 weeks (median 3, 14 and 26 days; p <10-10 for all comparisons). Thus, longer HVEM than currently used is needed for expanding its clinical value from diagnosis of nonepileptic or very frequent epileptic events to a presurgical tool for patients with drug-resistant epilepsy. Technical developments and further studies are warranted.